How students perceive the history class in basic education: reflections from the Brazilian Amazon (2022)
Objective: The objective of this article is to analyse how a group of 9th grade high school students in a public school located in the Brazilian Amazon perceive the contents of the history class. We focus on finding out how these students understand the function of the historical facts taught in class; what contents are recognized as the most and least important, and what is the purpose of studying this discipline. Originality/contribution: The research was carried out in the framework of the activities of the Programa Institucional de Bolsas de Iniciação Docente (PIBID) at the Faculty of History (FAHIST). A questionnaire was designed and applied to the students. The reflection is centered on the participants’responses, whose records have authorship status and show the importance of understanding the way students represent the contents taught in the history class. Method: 129 records obtained by means of a questionnaire applied to 9th grade high school students were analyzed quantitatively and qualitatively. Strategies/information collection: Within the qualitative method, the questionnaire technique was used. Ten of the twenty questions we proposed were "semi-open" with "yes-no" options and had a blank space to justify the answers. The other ten were "open-ended" questions about which school subject they liked the most, which contents they remembered studying, which subjects they considered the most important and the least relevant, what was the function of the contents taught in history class, among others. Conclusion: According to students' responses, contents taught in the history  class are associated with the acquisition of knowledge linked to the past. Students do not associate the history class with the present or the future. In terms of content, they point to topics related to the history of Brazil as the most important in the discipline.